Rapid and scalable ruthenium catalyzed meta-C–H alkylation enabled by resonant acoustic mixing - Dey, Arnab; Kancherla, Rajesh; Pal, Kuntal; Kloszewski, Nathan; Rueping, Magnus (Communications chemistry, 2024)
Synthetic chemistry approaches for direct C–H bond alkylation offers a promising alternative to traditional functional-group-centered strategies which often involve multi-step procedures and may suffer from a variety of challenges including scalability. Here, we introduce resonant mixing as an efficient method for meta -C–H alkylation of arenes using a Ru-catalyst, avoiding the need for bulk solvents, external temperature, or light. The described methodology is highly rapid, enabling multigram-scale synthesis of meta -alkylation products within a short reaction time and achieving a very high turnover frequency. The reaction operates via a radical mechanism and is characterized by its mild reaction conditions, substrate compatibility, and exceptional meta -selectivity, all while significantly reducing reaction times. Synthetic chemistry approaches for direct C–H bond alkylation offers a promising alternative to traditional functional-group-centered strategies which often involve multi-step procedures and may suffer from a variety of challenges including scalability. Here, the authors introduce resonant acoustic mixing as an efficient method for meta -C–H alkylation of arenes using a Ru-catalyst via a radical mechanism, avoiding the need for bulk solvents, external temperature, or light.